THE FECUNDITY OF THE FALSE TREVALLY , LACTARIUS LACTARIUV (BLOCH AND SCNEIDER ) ALONG THE KARWAR COAST - NEELAKANTAN, B; KUSUMA, M S; PAI, M V (Fishery Technology, 2017)
A clear knowledge of the reproductive potential or fecundity of a fish is quite an essential pre-requmte for the proper management andconservation of the resources. The fecundity studies are also undertaken to determine. the index of diversity dependent fact<;>r affecting. the population size (Simpson, 1951). Qasim & Qayyam (1963) have detailed the various pathways by which an understanding of fecundity could be used for fishery biological work. The ability of egg production varies within the individual hm1ts such as length, somatic weight, gonadial weight, volume of fish ecc.